Cloud-based parallel computing across multiple clusters in Julia - Carvalho Junior, Francisco H. de; Alencar, João Marcelo Uchôa de; Sales, Claro Henrique Silva (Anais do Simpósio Brasileiro de Linguagens de Programação (SBLP), 2024)
IaaS cloud providers are now a de facto alternative to HPC. They offer a rich catalog of virtual machine instances with high-end processors and accelerators connected through advanced network technology. This makes it possible to create cluster computing platforms rivaling the on-premises alternatives. This paper presents an Infrastructure as Code (IaC) approach to build parallel computing systems in Julia, both hardware and software elements, benefiting users of HPC applications in dynamic programming languages.